Argumentative ethics - Monsalve Solórzano, Alfonso (Estudios de Filosofía, 1993)
Perelman's idea of value as a notion that, though obscure, makes agreement possible within the universal audience (the set of present day adult and reasonable individuals) is applied here in order to propose an ethics that, on the one hand, overcomes the limitations of the type of monologic foundation inaugurated by Kant and defended at present by Rawls; and that, on the other hand, criticizes Habermas' purely dialogical model as being unfeasible.